Prevalence and determinants of HIV testing-seeking behaviors among women of reproductive age in Tanzania: analysis of the 2022 Demographic and health survey - Jackson Micheal Asingwire; Isaac isiko; Kuli Faith Rombe; Aaron Mwesigwa; Emmanuel Asher Ikwara; Haron Olot; Lenz Nwachinemere Okoro; Manankong Jane Precious Izunwanne; Blessing Onyinyechi Agunwa; Abdul Aziiz Bwana; William Yiga Kalemba; Ebuka Louis Anyamene (AIDS Research and Therapy)
Abstract Aim HIV remains one of the major epidemics and public health concerns within low and middle-income countries such as Tanzania. This study aimed to assess the prevalence and the factors associated with HIV testing-seeking behaviors among women of childbearing age in Tanzania. Methods This study used the 2022 Tanzania Demographic and Health Survey dataset. The study utilized individual recodes (IR) files where data was collected using the Women’s Questionnaire to analyze factors influencing HIV testing behavior among women, Descriptive analysis, and bivariate and multivariate logistic regressions were performed and all the data were processed and analyzed using STATA version 17 at 95% CI and significance level P < 0.05. Results This study included 2531 women with 90.0% having ever tested for HIV while 7.0% had never tested for HIV. Not employed [AOR:0.35, CI (0.20–0.61)] has lower odds of HIV testing than All-year employed status. Rural residents have reduced odds of HIV testing [AOR:0.43, CI (0.21–0.88)] compared to women living in urban areas. Those able to ask their partner to use a condom are more likely to have been tested with increased odds [AOR: 3.52, CI (2.31–5.37)]. Participants with a history of genital discharge [AOR:4.30, CI (1.28–14.46)] and those who don’t know their genital discharge history have [AOR: 0.20, CI (0.07–0.55)] are significant for HIV testing. Women who have heard about PrEP but are not uncertain about its approval [AOR: 36.07, CI (3.33–390.25)], respondents who have tested before with HIV testing kits [AOR:35.99, CI (4.00–324.13)] and women who are aware of HIV testing kids but never tested with them before [AOR: 2.80, CI (1.19–6.58)] are predictors of HIV testing seeking behaviors. Conclusion The government and other concerned agencies should introduce mobile or community-based testing units and subsidize testing costs to reach economically disadvantaged or rural populations. Promote Open Communication on Sexual Health: Public health campaigns should encourage open discussions about sexual health within relationships, emphasizing condom negotiation and mutual health checks as preventive measures. Raise Awareness and Accessibility of HIV Prevention Tools: Expand education on PrEP and HIV self-test kits to improve familiarity and acceptance, which may empower individuals to proactively seek testing. Integrate Sexual Health Screening into Routine Healthcare: Health facilities should incorporate HIV testing when individuals present with symptoms like genital discharge to improve early detection and intervention.